Allenamides Playing Domino: A Redox‐Neutral Photocatalytic Synthesis of Functionalized 2‐Aminofurans. Issue 2 (18th October 2021) - Quintavalla, Arianna; Veronesi, Ruben; Speziali, Laura; Martinelli, Ada; Zaccheroni, Nelsi; Mummolo, Liviana; Lombardo, Marco
Abstract: A photoredox catalytic synthesis of functionalized 2‐aminofurans is proposed starting from α‐halo carbonyl substrates and N ‐allenamides. The protocol proves to be efficient and sustainable thanks to: i ) the use of visible light as green energy source, ii ) the redox‐neutral nature of the transformation, allowing to avoid additives and strong oxidants, iii ) the mild reaction conditions and the functional groups tolerance, iv ) the low photocatalyst loading and the absence of excess reagents, v ) the one‐pot formation of three new bonds in a domino sequence. According to our mechanistic hypothesis, the transformation is configured as a double radical‐polar crossover reaction, in which the photocatalyst is excited, oxidized and reduced twice for each molecule of 2‐aminofuran produced. The novelty of the designed synthetic approach also lies in the use of N ‐allenamides as substrates, which, after the addition of the first electrophilic radical, preserve a further reactive π‐system, making possible the addition of a second α‐keto radical and enabling the installation of a keto functionality at a remote position. The good yields, the broad scope, and the possibility to further synthetically elaborate the obtained furans make this protocol particularly promising for the construction of useful products. Abstract :